Mathematics and physics for nanotechnology : technical tools and modelling - Sia, Paolo Di (Singapore : Pan Stanford, 2019)
Nanobiotechnology is a new interdisciplinary science with revolutionary perspectives arising from the fact that at nanosize the behaviour and characteristics of matter change with respect to ordinary macroscopic dimensions. Nanotechnology is a new way for producing and getting materials, structures and devices with greatly improved or completely new properties and functionalities. This book provides an introductory overview of the nanobiotechnology world along with a general technical framework about mathematical modelling through which we today study the phenomena of charge transport at the nanometer level. Although it is not a purely mathematics or physics book, it introduces the basic mathematical and physical notions that are important and necessary for theory and applications in nanobiotechnology. Therefore, it can be considered an extended formulary of basic and advanced concepts. It can be the starting point for discussions and insights and can be used for further developments in mathematical-physical modelling linked to the nanobiotechnology world. The book is dedicated to all those who follow their ideas in life and pursue their choices with determination and firmness, in a free and independent way.
7: Functions of One Complex Variable7.1 Complex Numbers; 7.2 Basic Operations with Complex Numbers; 7.3 Polar Form of a Complex Number; 7.4 De Moivre's Theorem and Roots of Complex Numbers; 7.5 Functions of a Complex Variable; 7.6 Limits and Continuity; 7.7 Derivatives and Analytic Functions; 7.8 Cauchy-Riemann Conditions; 7.9 Harmonic Functions; 7.10 Singular Points; 7.11 Complex Elementary Functions; 8: Complex Integration; 8.1 Line Integrals in the Complex Plane; 8.2 Cauchy's Integral Theorem; 8.3 Cauchy's Integral Formula; 8.4 Series Representations of Analytic Functions
OCLC-licensed vendor bibliographic record.
Keywords: Nanobiotechnology; Nanotechnology; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; SCIENCE / Nanostructures; SCIENCE / Physics; TECHNOLOGY / Electronics / Optoelectronics